2019
DOI: 10.1021/acs.analchem.9b04638
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Critical Micelle Concentration of Surfactants by a Simple and Fast Titration Method

Abstract: Critical micelle concentration (CMC) is a crucial parameter of widely used surfactants, and many methods have been developed for CMC determination. However, the current methods for CMC determination, such as conductive, surface tension, and fluorometric methods, are tedious and time-and sample-consuming because a series of samples with different concentrations of surfactants need to be prepared and measured. Although an economical, simple, and fast titration method for CMC determination (only one sample and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 45 publications
(60 reference statements)
2
33
0
1
Order By: Relevance
“…[35] which makes calculation of micelles concentration in complex mixtures difficult. [39][40][41] It is known, however, that CMC values tend to increase with the hydrophilic nature of the surfactant and that nonionic surfactants that are insoluble in water may not generate micelles at all, especially in presence of a dispersed organic phase. [42] Some CMC values are reported by the respective stabilizer manufacturers, as described in the section that describes the manipulated materials.…”
Section: Particles Produced By Sonifiermentioning
confidence: 99%
“…[35] which makes calculation of micelles concentration in complex mixtures difficult. [39][40][41] It is known, however, that CMC values tend to increase with the hydrophilic nature of the surfactant and that nonionic surfactants that are insoluble in water may not generate micelles at all, especially in presence of a dispersed organic phase. [42] Some CMC values are reported by the respective stabilizer manufacturers, as described in the section that describes the manipulated materials.…”
Section: Particles Produced By Sonifiermentioning
confidence: 99%
“…of chemical (fluorescent) probes, the need for expensive and/or complicated equipment, requirement of additional computational add-ons, and/or methods are time-and sample-consuming because a series of surfactant solutions with different concentrations must be prepared and characterized individually. [8][9][10][11] The development of novel responsive and triggerable materials combined with advances in imaging techniques hold promise to provide alternative cost-effective, rapid, and material gentle pathways for visualizing detectable changes of physical parameters in surfactant solutions and thus to circumvent complications associated with conventional techniques. In this context, liquidliquid transduction schemes, such as oil-in-water emulsions are appealing because they allow the investigation of surfactants within their designated environment.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of THPscompletely no emission in surfactant micelles but strong AIE in dilute surfactant solutions-let us develop them as unique sensitive and visible fluorescence-turn-on (showing the strongest fluorescence at CMC) probes for CMC (the reported CMC probes based on fluorescence intensity change show fluorescence-turn-off change at CMC, that is, show the weakest fluorescence at CMC) [26,27]. Recently, we found that one of the THPs could be used as an excellent indicator for CMC titration and realized simple, sample-and time-saving CMC titration for different kinds of surfactants for the first time [28].…”
Section: Introductionmentioning
confidence: 99%